Machine Learning for Text Analysis: A Systematic Review - Mayte MODESTO-JAVIER; Smart VELÁSQUEZ-TAMAYO; Javier GAMBOA-CRUZADO; Guillermo PAUCAR-CARLOS; Juan GAMARRA-MORENOand Fernando SINCHE CRISPÍN (Communications of International Proceedings, 2020)
Text analysis is a fundamental tool in the development of education. However, UNESCO figures indicate that the majority of children have comprehension difficulties, which can result in reasoning problems, difficulty in understanding the theory, and gaining knowledge. This article presents a systematic review of the literature (SRL) regarding text analysis and the use of machine learning (ML) to improve this process. The results indicate that ML learning techniques are effective in the improvement of text analysis.
Keywords: Machine Learning; Text Analysis; Natural Language Processing; Systematic Literature Review.